PENGARUH METODE OUTDOOR LEARNING TERHADAP KEMAMPUAN MENULIS DESKRIPSI SISWA KELAS IV SDN 98 BONTOMANAI KABUPATEN BULUKUMBA - Tenri Deapati; Prof. Sulfasyah, S.Pd., M.Pd., Ph.D; Dr. Anzar, S.Pd., M.Pd (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The main problem in this study is whether the outdoor learning method has aninfluence on the descriptive writing ability of fourth grade students of SDN 98Bontomanai. This researcher aims to determine the effect of the application of theoutdoor learning method on the descriptive writing ability of fourth grade studentsof SDN 98 Bontomanai. This study uses a quantitative approach with a pre-experimental design type one group pretest-posttest design. The sample in thisstudy amounted to 30 students. Data collection was carried out using the results ofthe descriptive essay writing assessment. The data obtained were then analyzedusing statistical analysis techniques, namely descriptive statistics and inferentialstatistics. After analyzing the data, the author found that the learning outcomes ofstudents before using the outdoor learning method were relatively low, namely theaverage value of the pre-test results was 49.23, then the average value of thepost-test results was 66.9. After obtaining Tcount 7.82 and Ttable 1.699, it wasobtained t_(Count)> t_Table or 7.82> 1.699 Based on the results of tCount andtTable, it can be concluded that the use of the outdoor learning method has aneffect on the ability to write descriptions of grade IV students of SDN 98Bontomanai.